THE TEACHERS’ EXPERIENCE BACKGROUND AND THEIR PROFESIONALISM - Yulyanti Harisman; Yaya Sukjaya Kusumah; Kusnandi Kusnandi; Muchamad Subali Noto (Jurnal Infinity, 2019)
Based on literature review Three categories of teachers are: good, very good, and excellent which are viewed from aspects of beliefs, attitude, depth of pedagogical and didactic aspects, and teacher reflection in the learning process has been obtained in previous studies. Various external aspects are considered to affect teacher professionalism in learning about mathematical problem solving. These aspects need to be studied to maximize the teacher professionalism. This study will examine these external aspects, ranging from teaching experience, educational background, and experience in participating in training to improve teacher competencies. This type of qualitative research with survey methods was chosen as a research method. Three teachers from three junior high schools with different clusters were selected as research subjects. Each teacher is given short questions related to this. The results obtained are the experiences of the trainings that teachers follow in increasing their competence and teacher's educational background have more significant influence on teacher professionalism compared to the experience or length of teacher teaching.